Pendugaan Parameter Genetik Ketahanan Tanaman Cabai terhadap Penyakit Antraknosa - Syaidatul Rosidah; Muhamad Syukur; Widodo Widodo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Fruits of chili pepper as crossing population between C15 and C2 genotype were used to study genetic parameter of resistance for anthracnose disease caused by Colletotrichum acutatum. Twenty mature green chili pepper fruits from each plant were inoculated by C. acutatum PYK 04 isolate. The results showed that resistance to anthracnose in chili pepper was controlled by recessive gene. Broad-sence heritability were high for both disease incidence and necrotic diameter. Narrow-sence heritability were high for stem diameter and low for necrotic diameter. Additive-variance ratio were high for disease incidence and medium for necrotic diameter. Development of resistance varieties of chili pepper to anthracnose should be subjected to line varieties.